Macroeconomics : theories & policies - Froyen, Richard T. (Upper Saddle River, NJ : Prentice Hall, 1996)
The book includes an up-to-date summary of the Keynesian position, including resent research that has come to be called the new Keynesian economics and extensive treatment of monetary policy.
Includes bibliographical references and index.
uaj 15/04/2015
Loan
Keywords: Macroeconomics; Macroeconomics- theory; Macroeconomics- policies